DIGITAL CHALLENGES OF LOCAL MEDIA OF THE NIŠAVA DISTRICT - Mihajlov Prokopović, Anka M; Jevtović, Zoran; Jovanović, Zoran (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2020)
This text presents the main results of the project “Local Media of the Nišava District in the Digital Age“. The subject of the research was the position of the local media of the Nišava district, as well as the capacities and strategies that these media have in order to meet the challenges posed by the digital age. The aim of the project was to explore the economic, social and technological position of the local media of the Nišava District and their ability to develop as institutions of the local public sphere in the digital environment. The answer to the research question: “How the local media of the Nišava District adapt to the changes brought by the digital age“ was obtained by applying two methodological procedures. The first is the implementation of in-depth interviews with the editors-in-chief of 20 local media in the Nišava District, who provided information on the economic position of local media, staffing, technological and organizational structures of local media, attitudes toward public interest and development strategies. The second methodological procedure is the analysis of the content of online editions of traditional local media and digital only local media in the Nišava District, which has established the level of development of these sites. The conclusion of this research is that the media that originate and live only on the Internet showed greater innovation, while the editors-in-chief of traditional local media primarily strive to improve their traditional media and therefore to develop a strategy of 'necessary minimum presence' in the online sphere.
Keywords: local media; online journalism; journalism; future of journalism; Serbia